Factors influencing career interest in becoming a public accountant - Afiifah, Vicka Juan; Putri, Eskasari (Institute of Computer Science (IOCS), 2025)
This study investigates the factors influencing students' interest in pursuing a career as a public accountant, focusing on financial rewards, labor market considerations, social values, professional training, and professional recognition. A quantitative approach is utilized, with a sample of 91 accounting students from the 2021 and 2022 cohorts at Universitas Muhammadiyah Surakarta, selected through purposive sampling. Data collection is conducted via online questionnaires using a five-point Likert scale. The analysis includes descriptive statistics, validity and reliability tests, and classical assumption tests to ensure unbiased results. Hypothesis testing employs multiple regression analysis, with t-tests examining individual variable effects, F-tests assessing overall model significance, and R² determining explanatory power. Findings reveal that financial rewards, social values, professional training, and professional recognition significantly influence career interest in public accounting, while labor market considerations do not. The study's limitations include a restricted sample, which may limit generalizability, and the exclusion of other potential influencing factors. Future research should consider additional variables, such as gender, workplace environment, and family background, while also expanding the sample to encompass students from multiple universities for broader applicability.